Threshold effects of bone mineral density on mortality risk: a comprehensive analysis of BMI-mediated pathways in older population - Yin, Zifei; Kuang, Chen; Gao, Feng; Xu, Feng (Frontiers in Endocrinology, 2025)
BackgroundThe precise relationship between bone mineral density (BMD) and all-cause mortality in older adults remains incompletely understood. This study aimed to investigate the association between BMD and all-cause mortality and to explore the mediating role of body mass index (BMI) in adults aged ≥60 years.MethodsA cohort study was conducted using data from the National Health and Nutrition Examination Survey (2007–2010, 2013–2014, and 2017–2018), including 6,289 participants aged ≥60 years. The application of Cox proportional hazards models enabled the evaluation of the association between BMD and all-cause mortality, while causal mediation analysis was performed to assess the mediating effect of BMI.ResultsThis study revealed that among the 6,289 participants, 1,422 (22.61%) deaths occurred during the follow-up period. The findings showed that there was a J-shaped association between BMD and all-cause mortality, with an increased mortality risk observed as BMD decreased. Higher BMD was associated with lower mortality risk, with evidence suggesting both direct and BMI-related pathways. The total effect was strongest for total femur BMD (-0.056, P<0.0001), followed by intertrochanter (-0.061, P<0.0001), trochanter (-0.043, P<0.0001), and femoral neck (-0.025, P=0.002). BMI appeared to partially mediate the protective associations, with varying proportions observed across sites: femoral neck (24.18%), trochanter (12.83%), total femur (11.17%), and intertrochanter (9.20%). The pathway analysis revealed that BMI was found to partially mediate the association between BMD and all-cause mortality. These associations remained robust after adjusting for demographic, socioeconomic, and clinical confounding factorsConclusionsThis study identified site-specific threshold effects of BMD on mortality and quantified the mediating role of BMI. The findings suggest that maintaining an optimal BMI may be associated with reduced mortality risk for individuals with low BMD. Integrated interventions targeting both bone density and body mass management could be more effective in reducing mortality risk among older adults with low BMD.